2016
DOI: 10.1016/j.jcma.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ticagrelor versus clopidogrel in acute coronary syndrome in Taiwan: A multicenter retrospective pilot study

Abstract: Ticagrelor treatment could provide a marginally favorable effect at the expense of an increased risk of dyspnea in real-life situations. This pilot study provides a scientific basis to call for a larger, suitably powered Phase 4 prospective or observational study in this ethnic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
2
35
1
Order By: Relevance
“…Only limited data exist on the comparison between the newer P2Y12 inhibitors (prasugrel and ticagrelor) and clopidogrel in East Asian patients with ACS. [20][21][22][23] The PHILO trial, which was designed to mirror PLATO, was a multicenter, randomized, double-blind, non-event-driven study conducted in Japan and East Asian countries (Japan, 90%; Taiwan, 4%). 21 The incidence of primary efficacy endpoints was 10.2% per year with ticagrelor and 8.1% per year with clopidogrel (HR, 1.47; 95% CI: 0.88-2.44).…”
Section: Discussionmentioning
confidence: 99%
“…Only limited data exist on the comparison between the newer P2Y12 inhibitors (prasugrel and ticagrelor) and clopidogrel in East Asian patients with ACS. [20][21][22][23] The PHILO trial, which was designed to mirror PLATO, was a multicenter, randomized, double-blind, non-event-driven study conducted in Japan and East Asian countries (Japan, 90%; Taiwan, 4%). 21 The incidence of primary efficacy endpoints was 10.2% per year with ticagrelor and 8.1% per year with clopidogrel (HR, 1.47; 95% CI: 0.88-2.44).…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial[ 6 ] and meta-analysis[ 7 ] demonstrated that ticagrelor was no longer superior over clopidogrel in efficiency, with increased major bleeding. Whereas, two observational studies reported that ticagrelor offered significantly or marginally better anti-ischemic protection than clopidogrel in ACS[ 8 ] or AMI[ 9 ] patients, both without an increase in the rate of major bleeding. The above evidence implied that some critical factor might be closely involved in the efficacy of ticagrelor, which was special in East Asian patients and was changed when ticagrelor was applied from Phase III RCTs to the real-world clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent meta-analysis,[ 7 ] which focused on the population of East Asia, also demonstrated no advantage of ticagrelor on antithrombotic efficiency. Whereas, two recent real-world studies reported that ticagrelor could provide a marginally or significantly favorable antithrombotic efficacy in patients with ACS[ 8 ] or acute myocardial infarction (AMI),[ 9 ] both with similar major bleeding rates compared with clopidogrel. These contradictory results have caused considerable confusion regarding the efficacy of ticagrelor, providing the impetus to formulate better antiplatelet strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies indicated that ticagrelor was no longer superior over clopidogrel in efficacy and was associated with increased bleeding risk 16,28 . These studies implied that East Asian patients may have different features that influence the response to antiplatelet agents and related clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of MVD has been associated with an elevated risk of high platelet reactivity (HPR) after clopidogrel treatment 18 and a higher hazard of MACE, 30 no studies have investigated the role of MVD on the relative efficacies of antiplatelet therapies. Previous studies comparing different antiplatelet therapies have examined potential effect modifiers by subgroup analysis, that is calculating the HR conditioning on a third clinical variable (such as age, sex, and comorbidities) 16,28 . However, the set of stratification variables in the subgroup analyses were selected a priori, and some potential effect modifiers beyond the current knowledge—such as the number of diseased vessels—may thus have been left unexamined.…”
Section: Discussionmentioning
confidence: 99%